Insights on the role of primary and secondary tar reactions in soot inception during fast pyrolysis of coal. (1st September 2020) - Apicella, B.; Russo, C.; Cerciello, F.; Stanzione, F.; Ciajolo, A.; Scherer, V.; Senneca, O.
Graphical abstract: Highlights: Data on chemical composition of primary tar are mandatory for understanding pyrolysis. Secondary reactions of tar are a source of PAH which in turn can be soot precursors. Soot formation is highly limited when primary tar is immediately quenched. The limitation of secondary tar reactions reduces soot emissions with health benefits. Abstract: In the present work fast pyrolysis of coal in N2 and CO2 atmospheres was studied in a drop tube reactor (DTR) and in a heated strip reactor (HSR). In the DTR the volatiles generated by coal pyrolysis were entrained in a hot gas stream and were collected at the reactor outlet by tar traps. In the HSR, the volatiles were ejected from the hot coal particles into a cool environment and the condensable species, including primary tar, deposited and/or condensed on a glass bridge located above the heated strip. The composition of tars produced in the two reactors was compared to study the role of gas tar reactions in soot inception, and reference compounds for each class of tar species produced were identified. In the DTR the formation and growth of polycyclic aromatic hydrocarbons (PAH) were found higher than in the HSR. Soot formation occurred only in the DTR, being negligible in the HSR. It was concluded that the hot gas environment of the DTR favours secondary tar reactions, formation of PAH and eventually soot, while in the HSR this path was prevented due to prompt cooling down of volatiles. The presence of large concentration of CO2 in the pyrolysis atmospheres further promoted formation of heavy PAH and soot in the DTR, but not in the HSR, where the cooler environment limits soot-CO2 reactions in the gas phase.